2019
DOI: 10.1177/0886260519855663
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of the Perspectives of Domestic Violence Survivors on Behavior Change Programs With Perpetrators

Abstract: This study investigated the process of change in Intimate Partner Violence (IPV) perpetrators through in-depth interviews with their (ex-) partners. Programmes designed to help perpetrators change their behaviour, have yet to be endorsed by rigorous evaluation. In this context, this study explored survivors' perspectives for direction on how these programmes might be further developed. Interviews were conducted with eighteen IPV survivors, who had recently had the experience of having a (ex-) partner complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…Survivors described the need for long‐term sustained change in perpetrators and genuine feelings of safety for themselves and their children (McGinn, Taylor, & McColgan, 2019). Court‐ordered participants to Batterer Intervention Programs (BIPs) learn to modify their attitudes and beliefs (Craig, Robyak, Torosian, & Hummer, 2006) by learning to ‘talk the talk’ to get credit for completing the program.…”
Section: Recent Intimate Partner Violence Researchmentioning
confidence: 99%
“…Survivors described the need for long‐term sustained change in perpetrators and genuine feelings of safety for themselves and their children (McGinn, Taylor, & McColgan, 2019). Court‐ordered participants to Batterer Intervention Programs (BIPs) learn to modify their attitudes and beliefs (Craig, Robyak, Torosian, & Hummer, 2006) by learning to ‘talk the talk’ to get credit for completing the program.…”
Section: Recent Intimate Partner Violence Researchmentioning
confidence: 99%
“…(Ex-)partners are first-hand informers of risks that the programme might arise or mitigate and of the changes that the perpetrator has undergone during the programme. It has been argued that the insights of first-hand informers might be more objective than ones from perpetrators (McGinn et al 2021), as the evidence has shown that men tend to underestimate their perpetration (Ackerman 2016;Hamby 2016;Myhill 2017). Despite this, the results from the Mirabal project showed that perpetrators' accounts were more reliable than previous research suggested; therefore, in our study, we included dyads to compare results, prioritising victims' reports.…”
Section: Introductionmentioning
confidence: 99%
“…As pointed out within the study of McGinn et al (2021), perpetrator programs can become perpetrator-centric and stray from their original conceptualisation as just one part of an integrated response to IPV. To avoid this, it is crucial to include measures of survivor safety and wellbeing as well as the impact and harm caused to victims in programme evaluations (Gondolf and Beeman 2003;McGinn et al 2021;Travers et al 2021). There are two main studies that have explored the impact of perpetrator programmes on women's and children's outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Existing literature shows that there has been little evidence-based research studying the effectiveness of current BCPs, even less data on post-program evaluations, and limited long-term impact evaluations (McGinn et al, 2019). There is a grey area within the field of domestic violence concerning BCPs, particularly in terms of what actually works and what needs to be changed and/or implemented.…”
Section: Introductionmentioning
confidence: 99%